First identification and pathogenicity study of Vibrio harveyi isolated from diseased American eel (Anguilla rostrata) cultivated in freshwater. (8th November 2021) - Wan, Qijuan; Wu, Liqun; Yang, Qiuhua; Lin, Mao; Guo, Songlin
Abstract: Diseases caused by Vibrio harveyi in marine organisms have been generally reported in aquaculture, but there has been no reported V .  harveyi infection in fish cultivated in freshwater. Herein, we isolated 3 strains of V .  harveyi from diseased American eels ( Anguilla rostrata ) cultivated in freshwater and subsequently confirmed the virulence of V .  harveyi and the extracellular product (ECP). The three isolates were identified as V .  harveyi based on phenotypic features and homology of 16S rDNA and 3 house‐keeping genes (HKGs). Experimental infection revealed that V .  harveyi and ECP were highly pathogenic to American eels, and the median lethal doses (LD50 ) were 1.67 × 10 3  cfu/g and 7.29 μg/g body weight, respectively. Moreover, our antibiotic susceptibility test showed that V .  harveyi was susceptible to 16 of 20 antibiotics using the VITEK system of Mérieux. Furthermore, liver and kidney samples were collected for paraffin sectioning, stained with haematoxylin–eosin (H & E) and Periodic Acid–Schiff (PAS). H & E staining results revealed hepatocyte atrophy and necrosis, hepatic intercellular haemorrhage and intrahepatic venous thrombosis, while the kidney was characterized by renal tubular epithelial cell swelling and renal interstitial haematopoietic cell loss. Interestingly, glycogen deposition was more obvious in the kidney compared with the liver after PAS staining. Cultivated eel infected by V .  harveyi i was reported for the first time, and the results of this study provide a valuable reference for further prevention and control of fish diseases caused by V .  harveyi .